ICT and the economy in the ASEAN region - Echiverri, Earle Kendric G.; Sotin, Soleil Christianne T.; Pernia, Ernesto M. (Quezon City School of Economics, University of the Philippines Diliman, 2023)
Our paper examines the role of ICT in the economic development of the ASEAN region. Using panel data on six ASEAN countries from 2000 to 2019, we analyze the impact of two ICT features, namely, mobile cellular and fixed broadband subscriptions, by applying ordinary least squares (OLS) fixed effects, random effects, and generalized least squares (GLS) regressions. Our results show that both ICT features have positive and significant effects on economic development as indicated by GDP growth.
Thesis (BS Economics) - - University of the Philippines Diliman
Keywords: Information technology -- Economic aspects -- Southeast Asia